2004
DOI: 10.2337/diabetes.53.7.1841
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Inducible Nitric Oxide Synthase Expression in Advanced Glycation End Product–Stimulated RAW 264.7 Cells

Abstract: Advanced glycation end products (AGEs) are closely linked to the development of diabetic atherosclerosis. The current study examines the induction of inducible nitric oxide (NO) synthase (iNOS) and heme oxygenase (HO)-1 expression by AGEs, as well as the signaling pathways involved and the interplay between these two enzymes. The stimulation of RAW 264.7 cells with 6.64 or 33.2 g/ml AGEs leads to HO-1 protein expression, iNOS protein expression, and nitrite accumulation. AGEs lead to the phosphorylation of p42… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
1
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(29 citation statements)
references
References 49 publications
0
26
1
2
Order By: Relevance
“…HO-1 is induced by a number of stressors, 7 and one may predict that risk factors for the development of coronary heart disease and other cardiovascular disease processes will mediate HO-1 expression. In fact, this is the case because increased blood pressure 22 and altered laminar flow in blood vessels, 23 advanced glycation end products, 24 cigarette smoke, 25 oxidized lipids, 26 and a multitude of systemic inflammatory processes 7 lead to increased cellular HO-1 expression. Moreover, this constellation of processes that lead to HO-1 induction may suggest a role for HO-1 in mediating the cardiovascular disease processes associated with obesity and metabolic syndrome, 27 which have become significant public health problems.…”
Section: Ho-1: Protection Against Atherosclerotic Diseasementioning
confidence: 99%
“…HO-1 is induced by a number of stressors, 7 and one may predict that risk factors for the development of coronary heart disease and other cardiovascular disease processes will mediate HO-1 expression. In fact, this is the case because increased blood pressure 22 and altered laminar flow in blood vessels, 23 advanced glycation end products, 24 cigarette smoke, 25 oxidized lipids, 26 and a multitude of systemic inflammatory processes 7 lead to increased cellular HO-1 expression. Moreover, this constellation of processes that lead to HO-1 induction may suggest a role for HO-1 in mediating the cardiovascular disease processes associated with obesity and metabolic syndrome, 27 which have become significant public health problems.…”
Section: Ho-1: Protection Against Atherosclerotic Diseasementioning
confidence: 99%
“…Several previous studies have shown the cytoprotective effect of HO-1 in response to various oxidative insults both in vitro and in vivo [29][30][31]. Inhibition of iNOS protein expression by HO-1 has been shown in macrophages and smooth muscle cells, however, the inhibitory mechanisms of HO-1 on iNOS gene expression is still unclear [32][33][34][35][36]. Lee et al [33] reported that HO-1 inhibited LPS-induced phosphorylation of IkBa protein and nuclear translocation of p65 subunit of NF-kB [33].…”
Section: Discussionmentioning
confidence: 97%
“…In fact, with trypsin pre-treatment and by blocking the interaction to RAGE, we observed significant decreased levels of NO and iNOS immunoreactivity suppression. Currently, to our knowledge, there are no literature data related to RAGE involvement in ßA nitrergic system activation; however, it has been demonstrated that RAGE linkage with other ligands, as advanced glycation-end products (AGE), stimulated iNOS expression in mouse macrophages (37), in murine endothelial cells (38), and in murine macrophages (39). AGE stimulation led to nitrite accumulation and iNOS protein expression, which were partially downregulated by preincubation with anti-RAGE antibody, suggesting the role of RAGE in AGE-induced nitrosative stress activation (39,40).…”
Section: Discussionmentioning
confidence: 99%